A influência de pilares híbridos à base de titânio sobre os parâmetros clínicos e radiográficos periimplantares: um ensaio clínico randomizado - Pamato, Saulo (2018)
Introduction: Although peri-implant bone remodeling is commonly expressed in survival rates, there is limited evidence of predisposing risk factors for marginal bone loss. While it is suggested that inflammatory parameters are important survival predictors, the discrepancy in the comprehension of periimplantitis has made it difficult to understand if should even be considered a disease or represent a complication due foreign body reaction. Objective: This randomized clinical trial aims to assess the influence of hybrid abutments on the peri-implant clinical and radiographic parameters around single crowns. Methods: 52 implants were placed in 21 patients. Subjects were randomly allocated into two groups according to the type of prosthetic abutment: cement-retained abutment (control, n=24) and hybrid abutment (test, n=28). The analysis of the peri-implant tissues was performed using a bleeding on probing, probing depth and marginal bone loss. Patients were followed up clinically and radiologically for regular reviews at loading (T1), and 6 and 12 months after prosthesis placement (T2 and T3, respectively). The bleeding on probing was examined by the non-parametric Mann-Whitney test, while the probing depth and marginal bone loss were submitted to repeated measures mixed ANOVA analysis. Positive correlation between the marginal bone loss and the implant anatomical characteristics was verified by Pearson's correlation analysis. In multivariate analysis, the relationship between the marginal bone loss and independent variables was performed by non-parametric Mann-Whitney and Kruskal-Wallis tests. Results: The marginal bone loss presented values of 1,15 0.82 mm (control group) and 1,23 0,79 mm (test group). There was no statistical significant difference between the groups (p=0,951). At the end of one-year follow-up, bleeding on probing and probing depth presented similar scores. No positive correlation was found between the marginal bone loss and the implant anatomical characteristics. Bivariate analysis revealed that the type of antagonist tooth and the receptor site affected marginal bone loss. Conclusion: The use of hybrid abutments did not favor the maintenance of peri-implant health, presenting similar results to observed in the cement-retained abutments.